In vitro studies show synergistic effects of a procoagulant bispecific antibody and bypassing agents. (15th July 2018) - Hartmann, R.; Feenstra, T.; Valentino, L.; Dockal, M.; Scheiflinger, F.
Abstract : Essentials Patients with hemophilia A and inhibitors receiving emicizumab experience breakthrough bleeding. Safety concerns may exist when combining emicizumab with bypassing agents. Combined bypassing agent and bispecific antibody increased thrombin generation up to 17‐fold. Thrombotic effects should be considered when combining emicizumab with plasma bypassing agent. Summary: Background: Investigational non‐factor products such as emicizumab offer a treatment option for patients with hemophilia and inhibitors. However, their mechanism of action raises questions regarding safety when they are combined with treatments for breakthrough bleeding. Objectives: To evaluate in vitro thrombin generation (TG) and clot formation for combinations of activated prothrombin complex concentrate (aPCC), recombinant activated factor VII (rFVIIa), and a sequence‐identical analog of emicizumab (SIA). Methods: Therapeutic concentrations of SIA (20–600 nm ) alone or with aPCC (0.05–1 U mL −1 ), isolated aPCC components or rFVIIa (0.88–5.25 μg mL −1 ) were tested for TG and compared with reference ranges for healthy donor plasma. Coagulation of FVIII‐inhibited blood was determined with a widely established method, i.e. rotational thromboelastometry (ROTEM), and confirmed with the Total Thrombus‐formation Analysis System. Results and conclusions: SIA (600 nm ) or aPCC (0.5 U mL −1 ) alone resulted in peak thrombin levels of 21.4 nm and 38.6 nm, respectively, both of which are lower than normal (83.7 ± 29.8 nm ). SIA plus aPCC (0.5 U mL −1 ) increased the peak thrombin level 17‐fold over SIA alone, exceeding the reference plasma value by 4.2‐fold. This hypercoagulable effect occurred with 600 nm SIA combined with as little as 0.25 U mL −1 aPCC, confirmed by ROTEM. FIX was the main driver for enhanced TG. SIA plus rFVIIa (1.75 μg mL −1 ) induced a 1.8‐fold increase in the peak thrombin level in platelet‐rich plasma, but it did not reach the normal range. These in vitro experiments demonstrate excessive TG after administration of a combination of aPCC and SIA at clinically relevant doses. Careful judgement may be required when breakthrough bleeding is treated in patients receiving emicizumab.